Latitudinal shift in the timing of flowering of tree species across tropical Africa: insights from field observations and herbarium collections. (1st July 2020) - Ouédraogo, Dakis-Yaoba; Hardy, Olivier J.; Doucet, Jean-Louis; Janssens, Steven B.; Wieringa, Jan J.; Stoffelen, Piet; Angoboy Ilondea, Bhely; Baya, Fidèle; Beeckman, Hans; Daïnou, Kasso; Dubiez, Emilien; Gourlet-Fleury, Sylvie; et al.
Abstract: Temporal and spatial patterns in flowering phenology were assessed for eight tropical African tree species. Specifically, the frequency and seasonality of flowering at seven sites in central Africa were determined using field data, graphical analysis and circular statistics. Additionally, spatial variation in the timing of flowering across species range was investigated using herbarium data, analysing the relative influence of latitude, longitude and timing of the dry season with a Bayesian circular generalized linear model. Annual flowering was found for 20 out of the 25 populations studied. For 21 populations located at the north of the climatic hinge flowering was occurring during the dry season. The analysis of herbarium collections revealed a significant shift in the timing of flowering with latitude for E. suaveolens, and with the timing of the dry season for M. excelsa (and to a lesser extent L. alata ), with the coexistence of two flowering peaks near the equator where the distribution of monthly rainfall is bimodal. For the other species, none of latitude, longitude or timing of the dry season had an effect on the timing of flowering. Our study highlights the need to identify the drivers of the flowering phenology of economically important African tree species.